China’s Bank Balance Sheet and Financing of Heterogeneous Enterprises - Kun Huang; Qiuge Yao (Economies, 2018)
Given the background of financial disintermediation and interest rate marketization, the assets of China’s commercial banks can be divided into traditional credit assets, whose rates of return are controlled by the supervision department, and financial assets, whose rates of return fluctuate according to market conditions. Direct financing enterprises are mainly state-owned enterprises with a good reputation, endorsed by the government, and they finance using the financial assets of commercial banks. Indirect financing enterprises are mainly private enterprises, which finance using credit assets. By introducing a financial intermediary sector with a balance sheet into dynamic stochastic general equilibrium (DSGE) model, our model endogenously determines the leverage ratio and the ratio of the two assets of the bank. Model results show that the impact from the volatility of financial markets and other exogenous shocks can affect the banks’ asset proportions of the two asset types, asymmetrically affecting the production scale of enterprises with two types of financing. Further, the bank’s leverage ratio changes will have a magnifying effect on economic fluctuations.